VD_FINDINFO HC / 2025 / 735 vom 23. September 2025 - VD Tribunal cantonal (2025)
EFFET SUSPENSIF, OBLIGATION D'ENTRETIEN, DOMMAGE IRRÉPARABLE, REJET DE LA DEMANDE | 315 al. 2 let. b CPC (CH), 315 al. 4 let. b CPC (CH)